Wet electrospinning-aided self-assembly of multifunctional GO-CNT@PCL core-shell nanocomposites with spider leg bioinspired hierarchical architectures. (12th April 2022) - Scaffaro, Roberto; Gammino, Michele; Maio, Andrea
Abstract: We report a fast route enabling the multiscale design of nanohybrid structures comprising a 3D fibrous network of polycaprolactone (PCL) wrapped by graphene oxide (GO) sheets onto which carbon nanotube (CNT) brushes are anchored. The method relies on electrospinning PCL solutions onto a suspension of GO and CNTs in ethanol. Self-assembly is due to electrostatic wrapping of GO sheets around PCL fibers and π-π stacking between GO and CNTs. Hierarchical architecture and nanopatterned surface allow gathering the starting properties of PCL, GO and CNTs into lightweight (99% porosity) yet robust (1575% stiffness improvement), amphiphilic monoliths that can remove methylene blue and/or methyl orange from stagnant water with ca.100% efficiency. Graphical abstract: Image 1